2014
DOI: 10.1016/j.jconrel.2014.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Progress of drug-loaded polymeric micelles into clinical studies

Abstract: Targeting tumors with long-circulating nano-scaled carriers is a promising strategy for systemic cancer treatment. Compared with free small therapeutic agents, nanocarriers can selectively accumulate in solid tumors through the enhanced permeability and retention (EPR) effect, which is characterized by leaky blood vessels and impaired lymphatic drainage in tumor tissues, and achieve superior therapeutic efficacy, while reducing side effects. In this way, drug-loaded polymeric micelles, i.e. self-assemblies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
538
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 729 publications
(560 citation statements)
references
References 112 publications
2
538
0
2
Order By: Relevance
“…Polymeric micelles constructed from polymeric prodrug of hydrophobic small molecular drugs have emerged as a very promising choice considering its good water solubility, easy to further modification, enhanced permeability and retention (EPR) effect, and tunable drug content. [18][19][20][21][22][23][24][25][26][27] Moreover, it was reported that the introduction of tumor-targeting moieties onto polymeric prodrugs can effectively enhance the accumulation in tumor tissues and therapeutic efficacy of drugs. 28 In this context, somatostatin receptors (SSTRs) were explored as potential targets because they are overexpressed in a variety of tumors and cancer cell lines, including breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric micelles constructed from polymeric prodrug of hydrophobic small molecular drugs have emerged as a very promising choice considering its good water solubility, easy to further modification, enhanced permeability and retention (EPR) effect, and tunable drug content. [18][19][20][21][22][23][24][25][26][27] Moreover, it was reported that the introduction of tumor-targeting moieties onto polymeric prodrugs can effectively enhance the accumulation in tumor tissues and therapeutic efficacy of drugs. 28 In this context, somatostatin receptors (SSTRs) were explored as potential targets because they are overexpressed in a variety of tumors and cancer cell lines, including breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, OX exhibits neurotoxicity, leading to chemotherapy-induced peripheral neuropathy 8,9 along with milder but similar side effects associated with cisplatin, which limit its clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…However, in general, because of structural complexity, direct evidence on the exact bonding mode of the (dach)Pt(II) moiety in the polymer conjugates was rarely reported. In most of the polymeric (dach)Pt(II) conjugates reported, 6,8,17 the (dach)Pt(II) cation was presumed to be linearly bonded to two separate carboxylate anions linked to the polymer backbone except for the (O, N) chelation by amino acid. 10 In this study, to confirm the bonding mode of the active (dach)Pt moiety to the linker AA connected to the spacer group AE of the polymer, we have simulated two different local environments of (dach) Pt Figure S3).…”
mentioning
confidence: 99%
“…10 Compared with conventional drug carriers, nanomaterials such as nanotubes, polymeric micelles, dendrimers, liposomes, and nanoparticles have several advantages, including a large surface area, ease of chemical modification, a small diameter for site-specific targeting of anticancer drugs, solubilization of lipophilic drugs, and physicochemical functionality. [8][9][10][11][12][13][14][15][16] For example, their large surface area and small particle size enable conjugation of cancer cell-targeting ligands, such as monoclonal antibodies, folic acid, and RGD peptides. [15][16][17][18] Among the nanomaterials, dendrimers have been extensively investigated in the biomedical field.…”
Section: Introductionmentioning
confidence: 99%